Perspective 85 : Art 16'85. - Art Basel Basel 1985; Endart-Löli; Keane, John; Maderna, Marianne; Maenz, Paul; Schneckenburger, Manfred; Stimm, Thomas; Stumpf, Manfred (Basel : Art Internationale Kunstmesse, 1985)
Baechler, Donald ; Endart-Löli ; Franchetti, Alessandro ; Keane, John ; Kogler, Peter ; Maderna, Marianne ; Mosbacher, Alois ; Sarmento, Julião ; Schifferle, Klaudia ; Sigurdsson, Sigrid ; Spaeti, Henri ; Stimm, Thomas ; Stumpf, Manfred ; Trawöger, Ernst ; Trockel, Rosemarie ; Wolf, Günter
Duits
Engels
Perspective 85 : Art 16'85, Basel, 12. - 17. Juni 1985
boek